Al Franken. God spoke [videorecording (DVD)] - Doob, Nick; Hegedus, Chris; Franken, Al; Coulter, Ann H.; Hannity, Sean, 1961- (Docurama ; Distributed by New Video Group, 2007)
A behind-the-scenes look at the life of the former Saturday Night Live comedian turned author, radio host, and political satirist.